Frequency and categorization of presleep fantasies - Anna Szente; Husamalddin Ali Alhour; Eszter Áfra; Ákos Arató; Barnabás Dudás; Anna Szűcs; Réka Horváth; Norbert Kovács; Gergely Darnai; József Janszky (Scientific Reports)
Abstract The content of presleep thoughts have been assumed to influence sleep quality for a long time, e.g., insomnia has repeatedly been discussed to be associated with anxious thoughts before falling asleep. However, the phenomenon of recurring, voluntary fantasizing before sleep does not appear to be a common research topic. In the first stage of this study, we explored the frequency of presleep fantasizing on a sample of 281 volunteers. In the second stage, we analyzed the content of ca. 5000 fantasy descriptions found online to discover similar patterns. Our results showed that approximately 75% of the respondents fantasizes before sleep regularly and could describe three main topics during categorization (‘aims and ambitions’, thinking about a ‘calming’ scene, ‘fading away and death’). Based on our findings, presleep fantasizing is a common phenomenon. To our knowledge, this is the first study to investigate and categorize presleep fantasies.